SOCIOLOGY OF SAFETY: PREVENTIVE MEASURES IN INSURANCE AS AN OBJECT OF ANALYSIS - Diana Kazbekova; Anel Yensebayeva; Elmira Otar; Kuralay Mukhambetova (Universitas Darussalam Gontor, 2024)
Modern sociology actively examines issues related to occupational safety and preventive measures in the field of insurance, with a specific focus on safeguarding the well-being and health of workers. This article presents a sociological analysis of preventive programs in insurance, paying close attention to their sociological dimensions. The study investigates the experiences and future prospects of countries belonging to both the Organization for Economic Co-operation and Development and the Eurasian Economic Union that have implemented preventive measures within their social insurance systems. The article discusses the key components of preventive programs, their role in guaranteeing worker safety and health, and the effectiveness of investments made in preventive measures. Furthermore, it presents data regarding the allocation of resources for preventive measures in different countries and evaluates the return on investment in preventive programs. In conclusion, the article highlights the significance of further developing and enhancing preventive programs in insurance to ensure the safety and well-being of workers in their respective work environments.